Anti-fingerprint and fingernail-mark-resistant protective film and preparation method thereof
By using a combination of nano-anti-fingerprint coating, self-repair coating, elastic polyurethane film layer and adhesive layer in the electronic product display protective film, the problem that the existing protective film cannot maintain anti-fingerprint, nail printing resistance, high definition and fit stability at the same time, achieving efficient anti-fingerprint and nail printing resistance effects, and avoiding edge curling problems.
Patent Information
- Application Number
- CN202411927733.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing electronic product display protective film cannot maintain high definition and fit stability while preventing fingerprints and nail printing, and is prone to edge curling problems.
The protective film consisting of a nano-anti-fingerprint coating, a self-repair coating, an elastic polyurethane film layer and an adhesive layer is adopted. The nano-anti-fingerprint layer is cured by cross-linking and curing of perfluorooctylpropyl acrylate and methyl methacrylate to form a dense and stable hydrophobic coating; the self-repair layer and the elastic polyurethane film layer are cross-linked and cured by the action of a photoinitiator to form a repair structure layer with a cross-linking structure; the adhesive layer is composed of acrylic resin, hydroxyacrylate monomer, etc., and has good adhesion stability and resilience.
It achieves excellent anti-fingerprint and nail printing performance while maintaining high definition and fit stability, and avoids edge curling problems.
Smart Images

Figure CN119736027A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of protective films, and more specifically, to an anti-fingerprint and anti-nail print protective film and a preparation method thereof. Background Art
[0002] The protective film for electronic product displays can protect the display screens of electronic products while maintaining the high definition of the mobile phone screen. It has the effects of scratch resistance, anti-fingerprint, and anti-nail mark, and can meet the user's needs in various environments.
[0003] In order to improve the anti-fingerprint and anti-nail mark performance of the protective film, some existing technologies solve the above problems by coating a self-repairing layer on the surface of the protective film and changing the thickness or hardness of the self-repairing layer. However, this method easily causes the edge warping of the protective film, affecting the stability of the fit between the protective film and the display screen. Some existing technologies also solve the anti-fingerprint and anti-nail mark problems by frosting the surface of the protective film or coating it with a frosted coating, but the clarity of the display screen is greatly reduced, affecting the texture of use. Summary of the invention
[0004] In order to solve the problem that the existing electronic product display screen protective film cannot have good anti-fingerprint and nail mark resistance while having high clarity and lamination stability, the present application provides an anti-fingerprint and nail mark resistant protective film and a preparation method thereof.
[0005] In a first aspect, the present application provides a protective film that is resistant to fingerprints and nail prints, using the following technical solution: A protective film that resists fingerprints and nail marks, comprising a nano anti-fingerprint coating, a self-repairing coating, an elastic polyurethane film layer and an adhesive layer, which are sequentially laminated from top to bottom, wherein the nano anti-fingerprint coating is a nano fluorine-containing coating, the self-repairing coating is a self-repairing polyurethane coating, and the adhesive layer is prepared by curing an adhesive, wherein the adhesive is prepared from the following raw materials in parts by weight: Acrylic resin 60-80 parts Hydroxyacrylate monomer 10-20 parts Dipentaerythritol hexaacrylate 5-8 parts 3-5 parts of cyclohexanedimethanol-1,4-diacrylate 2-6 parts of methyl methacrylate Isobornyl acrylate 1-5 parts Photoinitiator 3-6 parts 1-3 parts of antioxidants.
[0006] By adopting the above technical scheme, the protective film of the present application is composed of a nano anti-fingerprint coating, a self-repairing coating, an elastic polyurethane film layer and an adhesive layer. The nano anti-fingerprint layer has good hydrophobicity and anti-fingerprint properties, and will not affect the clarity of the protective film; the self-repairing layer, the elastic polyurethane film layer and the adhesive layer form a repair structure layer with good buffering and resilience, so that the protective film can quickly rebound the produced nail marks when scratched by nails. Among them, the adhesive layer is made of acrylic resin, hydroxy acrylate monomer, dipentaerythritol hexaacrylate, cyclohexanedimethanol-1,4-diacrylate, methyl methacrylate, acrylate isobornyl, photoinitiator and antioxidant. The adhesive layer prepared in this way has good adhesion stability and resilience, so that when the protective film is scratched by nails, it can cooperate with the elastic polyurethane film layer and the self-repairing coating to quickly rebound the nail marks, and at the same time can be stably attached to the surface of the display screen, while maintaining good clarity, there will be no problem of warping.
[0007] Preferably, the hydroxy acrylate monomer is composed of tris(2-hydroxyethyl)isocyanurate triacrylate and hydroxyethyl methacrylate in a weight ratio of (1-3):1.
[0008] By adopting the above technical scheme, the hydroxy acrylate monomer composed of tris(2-hydroxyethyl)isocyanurate triacrylate and hydroxyethyl methacrylate can improve the flexibility, adhesion and resilience of the adhesive layer, thereby improving the fingernail mark resistance of the protective film.
[0009] Preferably, the photoinitiator is a combination of at least two of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexyl phenyl ketone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0010] By adopting the above technical solution, the above photoinitiator can improve the cross-linking and curing efficiency of each component in the adhesive, thereby improving the bonding stability of the prepared adhesive layer and reducing the warping problem of the protective film.
[0011] Preferably, the thickness of the adhesive layer is 30-40 μm.
[0012] By adopting the above technical solution, the adhesive layer with a better thickness has better resilience as well as better bonding stability and clarity, reducing the problem of edge warping.
[0013] Preferably, the nano-fluorine-containing coating is prepared by curing a nano-fluorine-containing coating agent, and the nano-fluorine-containing coating agent is prepared from the following raw materials in parts by weight: Perfluorooctylpropyl acrylate 40-60 parts 8-12 parts of methyl methacrylate Nano silicon dioxide 5-10 parts 1-3 parts of heptadecafluorotriethoxysilane Benzoyl peroxide 0.05-0.15 parts.
[0014] By adopting the above technical scheme, perfluorooctylpropyl acrylate and methyl methacrylate are cross-linked and cured under the catalytic action of dibenzoyl peroxide to obtain a nano anti-fingerprint coating, which gives the protective film excellent hardness, hydrophobicity and anti-fingerprint properties, and effectively prevents fingerprint residue; nano silicon dioxide can be interwoven and dispersed in the cross-linking system of perfluorooctylpropyl acrylate and methyl methacrylate under the dispersing action of 17fluorodecyl triethoxysilane, and the nano anti-fingerprint coating obtained in this way has a dense and stable structure, which can further improve the hydrophobicity and anti-fingerprint properties of the prepared protective film, and at the same time will not affect the clarity of the protective film.
[0015] Preferably, the thickness of the nano-fluorine-containing coating is 1-5 μm.
[0016] By adopting the above technical solution, the nano-fluorine-containing coating with optimal thickness has better adhesion stability, hydrophobicity and anti-fingerprint properties, while avoiding the problem of the clarity of the protective film being affected by the coating being too thick.
[0017] Preferably, the self-repairing polyurethane coating is prepared by curing a self-repairing polyurethane agent, and the self-repairing polyurethane agent is prepared from the following raw materials in parts by weight: Polyurethane acrylate 40-60 parts 10-20 parts of diphenylmethane diisocyanate Hydroxyethyl acrylate 5-10 parts Photoinitiator 2-4 parts 1-2 servings of antioxidants.
[0018] By adopting the above technical scheme, polyurethane acrylate, diphenylmethane diisocyanate and hydroxyethyl acrylate produce a good synergistic effect. Under the action of the photoinitiator, they are cross-linked and cured to form a self-repairing polyurethane coating with a cross-linked structure. It has moderate hardness and excellent self-repairing ability, as well as high transparency and mechanical strength. The protective film can quickly return to its original state when scratched by nails, reducing residual nail marks, and at the same time can improve the adhesion stability of the nano-fluorine-containing coating on the surface of the elastic polyurethane film layer.
[0019] Preferably, the thickness of the self-healing polyurethane coating is 30-40 μm.
[0020] By adopting the above technical solution, the self-repairing polyurethane coating with optimal thickness enables the protective film to quickly return to its original state when scratched by nails, effectively reducing the generation of nail marks while improving the interlayer bonding stability of the protective film.
[0021] The elastic polyurethane film layer is prepared by curing an elastic polyurethane agent, and the elastic polyurethane agent is prepared from the following raw materials in parts by weight: Polyurethane acrylate 40-60 parts Hydroxyethyl acrylate 5-10 parts Photoinitiator 1-3 parts 1-2 servings of antioxidants.
[0022] By adopting the above technical solution, the elastic polyurethane film layer has better softness, cushioning and resilience than the self-repairing polyurethane coating, and can effectively absorb energy when the protective film is subjected to external impact, preventing damage caused by scratches by nails. At the same time, it also has good flexibility and adhesion, ensuring that the protective film will not warp during long-term use, so that the protective film can fit tightly to the display screen.
[0023] Preferably, the thickness of the elastic polyurethane film layer is 100-115 μm.
[0024] By adopting the above technical solution, the elastic polyurethane film layer with optimal thickness can ensure that the protective film has good buffering and resilience properties, effectively reducing the marks caused by nail scratches, while ensuring the stable fit between the protective film and the display screen to avoid the problem of warping.
[0025] In a second aspect, the present application provides a method for preparing an anti-fingerprint and anti-nail print protective film, using the following technical solution: A method for preparing a protective film that is resistant to fingerprints and nail prints, comprising the following steps: S1, preparing an elastic polyurethane film layer; S2, applying an adhesive to one side of the elastic polyurethane film layer, curing the adhesive to form an adhesive layer on the surface of the elastic polyurethane film layer; S3. A self-repairing coating and a nano anti-fingerprint coating are sequentially bonded on a side of the elastic polyurethane film layer away from the adhesive layer to obtain an anti-fingerprint and nail print-resistant protective film.
[0026] By adopting the above technical scheme, an elastic polyurethane film layer is first prepared, and then an adhesive is evenly coated on one side of the elastic polyurethane film layer and cured to form a strong adhesive layer. The self-repairing coating and the nano anti-fingerprint coating are sequentially bonded to the side of the elastic polyurethane film layer away from the adhesive layer, thereby improving the interlayer composite firmness of the self-repairing coating and the nano anti-fingerprint coating, and preventing them from separating and falling off.
[0027] In summary, this application has the following beneficial effects: 1. The anti-fingerprint and nail mark resistant protective film of the present application is composed of a nano anti-fingerprint coating, a self-repairing coating, an elastic polyurethane film layer and an adhesive layer. The nano anti-fingerprint layer has good hydrophobicity and anti-fingerprint properties, and will not affect the clarity of the protective film; the self-repairing layer, the elastic polyurethane film layer and the adhesive layer form a repair structure layer with good buffering and resilience properties, so that when the protective film is scratched by nails, it can quickly rebound to the nail marks produced. The protective film thus obtained has excellent anti-fingerprint and nail mark resistance effects, and at the same time has good clarity and fitting stability, and is not easy to warp.
[0028] 2. An adhesive layer is prepared with acrylic resin, hydroxy acrylate monomer, dipentaerythritol hexaacrylate, cyclohexanedimethanol-1,4-diacrylate, methyl methacrylate, isobornyl acrylate, a photoinitiator and an antioxidant. The adhesive layer prepared in this way has good adhesion stability and resilience, so that when the protective film is scratched by nails, it can cooperate with the elastic polyurethane film layer and the self-repairing coating to quickly rebound from the nail marks, and at the same time can stably adhere to the surface of the display screen, while maintaining good clarity and without the problem of warping.
[0029] 3. The hydroxy acrylate monomer composed of tris(2-hydroxyethyl)isocyanurate triacrylate and hydroxyethyl methacrylate in a preferred weight ratio can improve the flexibility, adhesion and resilience of the adhesive layer, thereby improving the nail mark resistance of the protective film.
[0030] 4. Polyurethane acrylate, diphenylmethane diisocyanate and hydroxyethyl acrylate produce a good synergistic effect, and under the action of a photoinitiator, cross-linking and curing are carried out to form a self-repairing polyurethane coating with a cross-linked structure; and polyurethane acrylate and hydroxyethyl acrylate produce a good synergistic effect, and under the action of a photoinitiator, cross-linking and curing are carried out to form an elastic polyurethane film layer with a cross-linked structure, and the nano anti-fingerprint coating obtained by curing with perfluorooctylpropyl acrylate, methyl methacrylate, nano-silica and heptadecafluorotriethoxysilane under the catalysis of dibenzoyl peroxide can cooperate with the adhesive layer of the present application, so that the prepared protective film has excellent anti-fingerprint and anti-nail print effects, and at the same time has good clarity and fitting stability, and is not easy to warp. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the layer structure of the anti-fingerprint and nail print resistant protective film of the present application.
[0032] Explanation of the accompanying drawings: 1. Nano anti-fingerprint coating; 2. Self-repairing coating; 3. Elastic polyurethane film layer; 4. Adhesive layer. DETAILED DESCRIPTION
[0033] The following is combined with Figure 1 The present application is further described in detail with reference to the accompanying drawings and embodiments.
[0034] The following are the sources and specifications of some raw materials of this application. The raw materials used in the preparation examples and embodiments of this application can be obtained from the market, including but not limited to the raw materials of the following models and manufacturers. Raw materials with equivalent performance can be used: 1. Acrylic resin: LENCOLO, L-6020; 2. Nano-silicon dioxide: gas phase nano-silicon dioxide, particle size 10-50nm; 3. Heptadecafluorotriethoxysilane: KH-1732; 4. Polyurethane acrylate: LENCOLO, L-8323.
[0035] Preparation example of adhesive Preparation Example 1 Preparation Example 1 discloses an adhesive prepared by the following steps: 6 kg of acrylic resin, 1 kg of hydroxy acrylate monomer (composed of hydroxyethyl methacrylate and β-hydroxypropyl acrylate in a weight ratio of 1:1), 0.8 kg of dipentaerythritol hexaacrylate, 0.3 kg of cyclohexanedimethanol-1,4-diacrylate, 0.2 kg of methyl methacrylate, and 0.5 kg of isobornyl acrylate were mixed for 20 minutes. After mixing evenly, 0.3 kg of photoinitiator (composed of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a weight ratio of 1:1) and 0.1 kg of antioxidant (composed of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1) were added and mixed for 10 minutes to prepare an adhesive.
[0036] Preparation Example 2-3 The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 1 below for details.
[0037] Table 1 Parameters of Preparation Examples 1-3 Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that the hydroxy acrylate monomer in Preparation Example 4 is composed of tris(2-hydroxyethyl)isocyanurate triacrylate and hydroxyethyl methacrylate in a weight ratio of 1:1, and the rest is the same as Preparation Example 1.
[0038] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that the hydroxy acrylate monomer in Preparation Example 5 is composed of tris(2-hydroxyethyl)isocyanurate triacrylate and hydroxyethyl methacrylate in a weight ratio of 3:1, and the rest is the same as Preparation Example 1.
[0039] Preparation Comparative Example 1 The difference between Preparation Comparative Example 1 and Preparation Example 1 is that cyclohexanedimethanol-1,4-diacrylate is replaced by dipentaerythritol hexaacrylate in an equal amount, and the rest is the same as Preparation Example 1.
[0040] Preparation Comparative Example 2 The difference between Preparation Comparative Example 2 and Preparation Example 1 is that an equal amount of dipentaerythritol hexaacrylate is replaced by a hydroxy acrylate monomer, and the rest is the same as Preparation Example 1.
[0041] Preparation Example of Elastic Polyurethane Agent Preparation Example 6 Preparation Example 6 discloses an elastic polyurethane agent, which is prepared by the following steps: 4 kg of polyurethane acrylate, 1 kg of hydroxyethyl acrylate, 0.1 kg of photoinitiator (composed of 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a weight ratio of 1:1) and 0.1 kg of antioxidant (composed of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1) are mixed for 20 minutes, and the mixture is mixed evenly to obtain an elastic polyurethane agent.
[0042] Preparation Example 7-8 The difference between Preparation Example 7-8 and Preparation Example 6 is that the amount of raw materials used and the preparation conditions are different, see Table 2 below for details.
[0043] Table 2 Parameters of Preparation Examples 6-8 Preparation example of self-repairing polyurethane agent Preparation Example 9 Preparation Example 9 discloses a self-healing polyurethane agent, which is prepared by the following steps: 4 kg of polyurethane acrylate, 1 kg of diphenylmethane diisocyanate, 1 kg of hydroxyethyl acrylate, 0.1 kg of photoinitiator (composed of 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a weight ratio of 1:1) and 0.1 kg of antioxidant (composed of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1), mixed for 20 minutes, mixed evenly, to obtain an elastic polyurethane agent.
[0044] Preparation Example 10-11 The difference between Preparation Example 10-11 and Preparation Example 9 is that the amount of raw materials used and the preparation conditions are different, see Table 3 below for details.
[0045] Table 3 Parameters of Preparation Examples 9-11 Preparation Example 12 The difference between Preparation Example 12 and Preparation Example 9 is that an equal amount of diphenylmethane diisocyanate is replaced by polyurethane acrylate, and the rest is the same as Preparation Example 9.
[0046] Preparation example of nano fluorine-containing coating agent Preparation Example 13 Preparation Example 13 discloses a nano fluorine-containing coating agent, which is prepared by the following steps: 4 kg of perfluorooctylpropyl acrylate, 0.8 kg of methyl methacrylate, 0.1 kg of heptadecafluorodecyl triethoxysilane, 0.5 kg of nano silicon dioxide and 0.005 kg of dibenzoyl peroxide are mixed uniformly to prepare a nano fluorine-containing coating agent.
[0047] Preparation Examples 14-15 The difference between Preparation Examples 14-15 and Preparation Example 13 is that the amounts of raw materials used and the preparation conditions are different, see Table 4 below for details.
[0048] Table 4 Parameters of Preparation Examples 13-15 Preparation Example 16 The difference between Preparation Example 16 and Preparation Example 13 is that an equal amount of heptadecafluorotriethoxysilane is replaced by vinyltrimethoxysilane, and the rest is the same as Preparation Example 13. Example
[0049] Example 1 Example 1 discloses a protective film that is resistant to fingerprints and nail prints, which is prepared by the following steps: S1, applying the elastic polyurethane agent prepared in Preparation Example 6 onto the first release film by double-roll extrusion coating, and then photocuring using a UV light curing device to prepare an elastic polyurethane film layer with a thickness of 100 μm; S2, applying the adhesive prepared in Preparation Example 2 to one side of the elastic polyurethane film layer by double-roll extrusion, attaching a second release film to one side of the adhesive, and then photocuring using a UV light curing device to form an adhesive layer with a thickness of 40 μm on the surface of the polyurethane film layer; S3, tear off the first release film on the surface of the elastic polyurethane film layer, use double-roll extrusion coating to apply the self-repairing polyurethane agent prepared in Preparation Example 9 on the side of the elastic polyurethane film layer away from the adhesive layer, and then use UV light curing equipment to photocuring to form a self-repairing coating with a thickness of 40 μm, and then apply the nano fluorine-containing coating agent prepared in Preparation Example 13 on the upper surface of the self-repairing coating, and dry it at a temperature of 100° C. to form a nano anti-fingerprint coating with a thickness of 1 μm, and then place the prepared protective film at a temperature of 25° C. for aging for 48 hours, and roll it up to prepare an anti-fingerprint and nail print-resistant protective film, see Figure 1 It should be noted that the UV light curing conditions mentioned above are all conventional UV light curing conditions and are not limited here.
[0050] Example 2-3 The difference between Example 2-3 and Example 1 is that the preparation process parameters are different, see Table 5 below for details.
[0051] Table 5 Parameters of Examples 1-3 Example 4 The difference between Example 4 and Example 1 is that the adhesive is derived from Preparation Example 4, and the rest is the same as Example 1.
[0052] Example 5 The difference between Example 5 and Example 1 is that the adhesive is derived from Preparation Example 5, and the rest is the same as Example 1.
[0053] Example 6 The difference between Example 6 and Example 1 is that the self-healing polyurethane agent comes from Preparation Example 12, and the rest is the same as Example 1.
[0054] Example 7 The difference between Example 7 and Example 1 is that the nano fluorine-containing coating agent comes from Preparation Example 16, and the rest is the same as Example 1.
[0055] Example 8 The difference between Example 8 and Example 1 is that the thickness of the elastic polyurethane film layer is 130 μm, the thickness of the self-healing polyurethane coating is 10 μm, and the rest is the same as Example 1.
[0056] Example 9 The difference between Example 9 and Example 1 is that the thickness of the self-healing polyurethane coating is 60 μm, and the rest is the same as Example 1.
[0057] Example 10 The difference between Example 10 and Example 1 is that the thickness of the adhesive layer is 10 μm, and the other aspects are the same as Example 1.
[0058] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the adhesive is derived from the preparation of Comparative Example 1, and the rest is the same as Example 1.
[0059] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the adhesive is derived from the preparation of Comparative Example 2, and the rest is the same as Example 1.
[0060] Performance testing The performance tests of the anti-fingerprint and anti-nail print protective films prepared in Examples 1-10 and Comparative Examples 1-2 are as follows: 1. Water drop angle test Use a water drop angle tester to place the protective film to be tested on the test platform and test the water drop angle, which is recorded as the water drop angle before wiping. Then use a dust-free cloth dipped in anhydrous ethanol to wipe the protective film back and forth three times. After the anhydrous ethanol evaporates, continue to test the water drop angle of the protective film, which is recorded as the water drop angle after wiping. Test and record the test results.
[0061] 2. Light transmittance test Use a transmittance tester, take glass as the carrier, test the transmittance of the glass and calibrate it, then stick the protective film on the glass surface to test the transmittance, test and record the test data.
[0062] 3. Nail print test Use a pressure testing machine with a load of 200g, and use a test nail to press down on the surface of the protective film. After holding for 2s, cancel the pressure and calculate the time it takes for the indentation produced by the test nail on the surface of the protective film to disappear. Test and record the test data.
[0063] 4. Warping test Stick the protective film on the glass surface of the display screen, place it in an incubator with a temperature of 85°C and a humidity of 85%, test it for 72 hours, observe whether the protective film has any edge warping, test it and record the test results.
[0064] The following are the performance test data of the anti-fingerprint and anti-nail print protective films prepared in Examples 1-10 and Comparative Examples 1-2, see Table 6 below for details.
[0065] Table 6 Performance data of Examples 1-10 and Comparative Examples 1-2 “ / ” means not tested.
[0066] In combination with Examples 1-3, Examples 4-5 and Example 10, Comparative Examples 1-2 and Table 6, it can be concluded that the adhesive layer prepared using the adhesive of the present application has good resilience and bonding stability, and can improve the nail mark resistance, light transmittance and adhesion performance of the protective film prepared. Compared with Example 1, Example 4-5 further optimizes the hydroxy acrylate monomer, the transmittance of the protective film obtained is improved, and the nail mark recovery time is shortened. In Comparative Example 1-2, the ratio of hydroxy acrylate monomer, dipentaerythritol hexaacrylate and cyclohexanedimethanol-1,4-diacrylate is changed, the transmittance of the protective film obtained is reduced, and the problem of warping occurs, and the nail mark recovery time is also significantly increased. This may be because hydroxy acrylate monomer, dipentaerythritol hexaacrylate and cyclohexanedimethanol-1,4-diacrylate have good synergistic effects, which can further improve the resilience and adhesion stability of the adhesive layer; and Example 10, compared with Example 1, reduces the thickness of the adhesive layer. Although the transmittance of the protective film obtained is slightly improved, the nail mark recovery time is significantly increased, and the problem of warping occurs. This may be because the resilience of the adhesive layer is reduced. Under the adhesion effect of the adhesive layer, the rebound time of the entire protective film is increased.
[0067] In combination with Examples 1-3 and 6, Examples 8-9 and Table 6, it can be concluded that the use of the self-repairing coating and the elastic polyurethane film layer prepared in this application for cooperation, and further optimizing the thickness of the self-repairing coating and the elastic polyurethane film layer, can further play a good synergistic role with the adhesive layer, thereby improving the nail print resistance of the prepared protective film, while improving the transmittance and warping problems. In Example 6, the diphenylmethane diisocyanate in the self-repairing coating was replaced with polyurethane acrylate, and the transmittance of the prepared protective film did not change much, but the nail print recovery time increased. It may be that there is no synergistic effect of the diphenylmethane diisocyanate and polyurethane acrylate, which reduces the flexibility of the self-repairing coating, thereby reducing the resilience of the prepared protective film. In Example 8, the thickness of the elastic polyurethane film layer is increased, the thickness of the self-repairing coating is reduced, and the nail print recovery time of the protective film is significantly increased. It may be because the self-repairing coating is too thin, which reduces the problem of nail print resistance. In Example 9, the thickness of the self-repairing coating is increased. Although the nail print recovery time is shortened, the problem of warping occurs.
[0068] Combining Examples 1-3 and Example 7 with Table 6, it can be concluded that the nano anti-fingerprint layer formed using the nano fluorine-containing coating agent of the present application has a good anti-fingerprint effect, and the water drop angle can reach 115-118°. Compared with Example 1, in Example 7, an equal amount of heptadecafluorotriethoxysilane in the nano fluorine-containing coating agent is replaced with vinyltrimethoxysilane, and the anti-fingerprint performance of the protective film obtained is reduced.
[0069] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A protective film that is resistant to fingerprints and nail prints, characterized in that: The invention comprises a nano anti-fingerprint coating, a self-repairing coating, an elastic polyurethane film layer and an adhesive layer which are sequentially laminated from top to bottom, wherein the nano anti-fingerprint coating is a nano fluorine-containing coating, the self-repairing coating is a self-repairing polyurethane coating, and the adhesive layer is prepared by curing an adhesive, and the adhesive is prepared from the following raw materials in parts by weight: Acrylic resin 60-80 parts Hydroxyacrylate monomer 10-20 parts Dipentaerythritol hexaacrylate 5-8 parts 3-5 parts of cyclohexanedimethanol-1,4-diacrylate 2-6 parts of methyl methacrylate Isobornyl acrylate 1-5 parts Photoinitiator 3-6 parts 1-3 parts of antioxidants.
2. The anti-fingerprint and anti-nail print protective film according to claim 1, characterized in that: The hydroxy acrylate monomer is composed of tris(2-hydroxyethyl)isocyanurate triacrylate and hydroxyethyl methacrylate in a weight ratio of (1-3):1, and the photoinitiator is a combination of at least two of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexyl phenyl ketone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
3. The anti-fingerprint and anti-nail print protective film according to claim 1, characterized in that: The thickness of the adhesive layer is 30-40 μm.
4. The anti-fingerprint and anti-nail print protective film according to claim 1, characterized in that: The nano-fluorine-containing coating is prepared by curing a nano-fluorine-containing coating agent, and the nano-fluorine-containing coating agent is prepared from the following raw materials in parts by weight: Perfluorooctylpropyl acrylate 40-60 parts Methyl methacrylate 8-12 parts Nano silicon dioxide 5-10 parts 1-3 parts of heptadecafluorotriethoxysilane Benzoyl peroxide 0.05-0.15 parts.
5. The anti-fingerprint and anti-nail print protective film according to claim 1, characterized in that: The thickness of the nano fluorine-containing coating is 1-5 μm.
6. The anti-fingerprint and anti-nail print protective film according to claim 1, characterized in that: The self-repairing polyurethane coating is prepared by curing a self-repairing polyurethane agent, and the self-repairing polyurethane agent is prepared from the following raw materials in parts by weight: Polyurethane acrylate 40-60 parts 10-20 parts of diphenylmethane diisocyanate Hydroxyethyl acrylate 5-10 parts Photoinitiator 2-4 parts 1-2 servings of antioxidants.
7. The anti-fingerprint and anti-nail print protective film according to claim 1, characterized in that: The thickness of the self-healing polyurethane coating is 30-40 μm.
8. The anti-fingerprint and anti-nail print protective film according to claim 1, characterized in that: The elastic polyurethane film layer is prepared by curing an elastic polyurethane agent, and the elastic polyurethane agent is prepared from the following raw materials in parts by weight: Polyurethane acrylate 40-60 parts Hydroxyethyl acrylate 5-10 parts Photoinitiator 1-3 parts 1-2 servings of antioxidants.
9. The anti-fingerprint and anti-nail print protective film according to claim 1, characterized in that: The thickness of the elastic polyurethane film layer is 100-115 μm.
10. A method for preparing an anti-fingerprint and anti-nail print protective film according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, preparing an elastic polyurethane film layer; S2, applying an adhesive to one side of the elastic polyurethane film layer, curing the adhesive to form an adhesive layer on the surface of the elastic polyurethane film layer; S3. A self-repairing coating and a nano anti-fingerprint coating are sequentially bonded on a side of the elastic polyurethane film layer away from the adhesive layer to obtain an anti-fingerprint and nail print-resistant protective film.
Citation Information
Patent Citations
Anti-fingerprint coating and preparation method thereof
CN103242691A
Optical adhesive tape, preparation method thereof and optical adhesive
CN110452620A
Protective film and preparation method therefor, laminating method, and terminal
WO2021164578A1
Cited By
Adhesive for color-changing alumite and preparation method thereof
CN120310478A
Self-repairing scratch-resistant coating, PVC decorative film and preparation method of self-repairing scratch-resistant coating
CN121022244A